The impact of autonomous driving in the ridesharing ecosystem - Costa, Manuel Leitão (2022)
This thesis wants to understand the impact of autonomous driving on the ecosystem of the Ridesharing Ecosystem. We start seeing how the technology works. Then we conclude that we are in a very concentrated industry and that digital trends are the path. The full potential of autonomous driving led to reductions in both operational and capital expenditures. The way forward will affect cost structures of owners-operators, the strategies, and relations between OEMs, technological companies, and TNC’s. Drivers will have to adapt to a new reality through education. New business models may arise with technology. In the end, a description of the requirements for this technology deployment the benefits for society.